Theoretical turns through tourism taste-scapes: the evolution of food tourism research - Sally Everett (Research in Hospitality Management, 2019)
This article reflects on the evolution of food tourism research by tracing its conceptual, theoretical and empirical twists and turns over the past few decades. Prompted by some recent systematic reviews of food tourism studies, I draw on literature to follow the journey of this multi-dimensional subject area as it has weaved between economic-focused positivistic traditions and more interpretative sociocultural perspectives. I suggest that food tourism research offers an illuminating conceptual vehicle which can be fostered to generate insightful understandings of the complexity and inter-connectedness of diverse culinary artefacts, identities and the experience of practised place. By exploring its roots, its growth and its potential future, I suggest it provides opportunities to pursue more interpretative and critical modes of thinking and furthers our understanding of concepts such as sustainability, performativity, embodiment, liminality and “in-betweenness”. In looking forward, I argue that food tourism research is still on a journey and while it continues to offer us a multifaceted cultural phenomenon saturated with meaning and discursive potential to produce new knowledge about tourism, we should embrace it, and travel with it.